1988
DOI: 10.1113/jphysiol.1988.sp017043
|View full text |Cite
|
Sign up to set email alerts
|

Voltage‐gated sodium and calcium currents in rat osteoblasts.

Abstract: SUMMARY1. The whole-cell voltage-clamp mode of the patch-clamp technique was used to investigate the presence of voltage-gated inward currents in osteoblasts from newborn rat calvaria.2. In K+-free solutions, three kinds of inward currents could be activated by depolarization: a voltage-gated Na+ current and two different types of Ca21 currents.3. The Na+ current was activated by depolarization above -40 mV in all the cells. It was reduced by half by 10 nM-TTX (tetrodotoxin).4. In an isotonic Ba2+ external sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(53 citation statements)
references
References 58 publications
(51 reference statements)
3
50
0
Order By: Relevance
“…The rapid increase of intracellular calcium concentration caused by vitamin D 3 analogues and other steroid hormones is an area of increasing investigation (2-13, 29, 30). 1␣,25-D 3 and its analogues rapidly activate inward calcium movement in osteoblasts or osteoblast-like cells (2)(3)(4)(5)(6)(7)12). Using acetoxymethyl Quin2 fluorescent calcium indicator, Lieberherr (6) concluded, based on inhibition by dihydropyridine drugs like nitrendipine, that 70% of the increase in intracellular calcium concentration caused by 1␣,25-D 3 was from calcium influx via L-type calcium channels, suggesting this is a major pathway for calcium influx.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The rapid increase of intracellular calcium concentration caused by vitamin D 3 analogues and other steroid hormones is an area of increasing investigation (2-13, 29, 30). 1␣,25-D 3 and its analogues rapidly activate inward calcium movement in osteoblasts or osteoblast-like cells (2)(3)(4)(5)(6)(7)12). Using acetoxymethyl Quin2 fluorescent calcium indicator, Lieberherr (6) concluded, based on inhibition by dihydropyridine drugs like nitrendipine, that 70% of the increase in intracellular calcium concentration caused by 1␣,25-D 3 was from calcium influx via L-type calcium channels, suggesting this is a major pathway for calcium influx.…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented by patch clamp recordings of whole-cell barium currents (2,3), by 45 Ca 2ϩ uptake (5,7), and by fluorescence measurements of intracellular calcium, using the calcium indicator acetoxymethyl Quin2 (10), that 1␣,25-D 3 (2) and other vitamin D 3 metabolites (3,5,7,8,(12)(13)(14) stimulate calcium influx into rat osteosarcoma cells (2,3,5,7,8,12,14) and human and rat osteoblasts (4,6) in primary culture. Guggino et al (15) and Caffrey and FarachCarson (2) have shown the presence of L-type calcium channels in ROS 17/2.8 osteoblast-like osteosarcoma cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…L-type VSCCs are the best studied Ca 2ϩ channel type and appear to be the major VSCC in osteoblasts, although T-type channels may be expressed transiently during development (36,37). Three types of cDNA sequences corresponding to ␣ 1S , ␣ 1C , and ␣ 1D were detected by Barry et al (8) in the rat UMR-106 osteosarcoma cell line.…”
Section: Figmentioning
confidence: 99%
“…That study revealed a receptor-operated Ca channel in the osteoblastic cell membrane. In addition, voltage-dependent Ca channels were demonstrated in the cell membrane of rat osteoblasts in culture (CHESNOY-MARCHAIS and FRITSCH, 1988). In both cases, a change in [Ca], due to Ca influx through the Ca channels is considered to be one of the early events of cell activation.…”
mentioning
confidence: 99%